PRKACA Mutations in Adrenal Adenomas: Genotype/Phenotype Correlations - Dalmazi, G. D.; Beuschlein, F. (Hormone and Metabolic Research, 2016)
Untargeted, next generation sequencing approaches have provided deep insights into genetic events that result in unopposed steroidogenesis from the adrenal cortex. In particular, somatic mutations in the gene encoding the catalytic subunit α of protein kinase A (PKA) (PRKACA) were identified independently by several groups as the most frequently altered gene in cortisol-producing adenomas. Detailed functional studies could explore the molecular consequences of these hot-spot mutations and large international cohorts have provided the basis to explore the clinical characteristics associated with this mutation. Thereby, PRKACA mutations are highly specific for cortisol over-secretion, while they are absent or very rare in the context of other adrenal diseases. Patients carrying these somatic mutations are affected by a more severe phenotype and are identified at a younger age. Thus, these genotype/phenotype correlations provide further evidence for the importance of PKA-dependent pathways for adrenal physiology and disease.
Keywords: adrenal tumor; adrenal cortex; cortisol; Cushing’s syndrome